Genetic and Non-Genetic Factors Influencing Fatty Acid Composition of Dairy Milk: A Review - Chaudhary, Rajni; Rai, Sweta; Sailo, Lalrengpuii; Farooq, Uiase Bin; Singh, Akansha; Naha, Binoy Chandra; Kumar, Amit (Indian Journal of Animal Nutrition, 2017)
Milk is a natural, complete and balanced food as it is a rich source of fat, protein, vitamins and minerals. On the same time, many surveys revealed that diet plays an important role as a risk factor for chronic diseases in humans. Prospective cohort studies have identified association between dietary fat type (like saturated fatty acid) and cardiovascular diseases. The concentration of milk fatty acids in ‘model’ milk fat for human health should contain <8% saturated fatty acids (SFA), <10% poly unsaturated fatty acids (PUFA), and >82% mono unsaturated fatty acids (MUFA). Although it may not possible to achieve this ‘model’ fat composition of milk and manipulation of milk composition fat is possible by altering the feed for dairy cows and through genetic interventions. Till date, major emphasis has been given to increase the amount of milk but in today’s scenario, more emphasis should be given to increase the quality of milk. The lower level of palmitic acid (C16: 0) in milk is desired in conjunction with an increase in the amount of cis MUFA and cis PUFA. The DGAT-1 gene (K232A allele) leads to an amino acid change i.e., a lysine to alanine substitution and associated with a higher fraction of C16: 0 in milk fat but less C14: 0, unsaturated C18: 0 and conjugated linoleic acid (CLA). Antioxidants, encapsulation or modified atmosphere packaging can be used to delay or avoid the phenomenon of oxidatio